Aloevera: The Miracle Plant and Its uses in Dentistry – A Review - Malvika Raghuvanshi1 , E.Rajesh2 , Shruti Sinha3 , N.Aravindha Babu4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aloevera has been in used by humans since times immemorial. Its health benefits are well known. AncientGreeks and Egyptians used it in their daily routine and in battle fields due to its many miraculous properties.Studies have proved the antiseptic, anti-inflammatory, anti-viral, anti-fungal and wound healing propertiesof aloe vera plant. Recently it has garnered a lot of interest regarding its use in dentistry as it is completelynatural and there are no side effects reported with proper usage. This paper gives an overview of the uses ofthis wonder plant in various departments of dentistry